Tantangan dan Solusi Penerapan Akuntansi Syariah di dalam Bisnis - Mega Yuwanda; Rayyan Firdaus (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
The application of sharia accounting in business is becoming increasingly relevant along with the growth of the global sharia economy. Sharia accounting, which is based on the principles of fairness, transparency and fair sharing of risks, offers a unique approach to financial management. This research uses a qualitative method based on literature review to explore the challenges, prospects and solutions for implementing sharia accounting in modern business. The research results show that the main challenges include limited competent human resources, sharia accounting standards that are not yet uniform, digitalization which requires technological adaptation, and a lack of social and cultural acceptance. On the other hand, the prospect of sharia accounting has great potential in increasing stakeholder trust, expanding access to sharia markets, and strengthening the company's ethical image. To overcome these challenges, solutions are needed such as the development of comprehensive sharia accounting standards, increasing human resource competence, investment in supporting technology, transformation of conventional paradigms, and multilateral cooperation between government, academics and the business sector. This research provides strategic insight into how sharia accounting can be applied effectively to support ethical and sustainable business growth.